Pembangunan Stock Monitoring Application untuk Pembuatan Laporan Goods in Transit Menggunakan Flask - Putra, Muhammad Al Frizal Deva Syach; Susetyo, Yeremia Alfa (Program Studi Teknik Informatika Universitas Pamulang, 2023)
PT XYZ is the largest retail company in Indonesia. PT XYZ is definitely inseparable from problems regarding stock items. The problem is generally about the difference in stock of goods that can occur due to the condition of goods in transit from the warehouse to the store or vice versa (Goods in Transit), goods lost on the way, or the store has not made a goods receipt report. One strategy to overcome this problem is to build a Stock Monitoring application for web-based Goods in Transit (GIT) report generation using the Flask Framework. The application is built using the Python programming language and the Waterfall method. The application of the MVC (Model, View, Controller) architecture of the Flask Framework and the Waterfall method can support the development of the Stock Monitoring application because the code settings are easy to manage and each process is carried out systematically so that the workflow becomes structured and easy. The result of this research is the application of the Flask Framework and the Waterfall method in the Stock Monitoring application which is used to generate GIT reports to overcome the problem of missing stock.